2018
DOI: 10.1111/jam.13766
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activities and pathogenesis-related genes expression in sunflower inbred lines affected bySclerotinia sclerotiorumculture filtrate

Abstract: The time of antioxidant system activation in host is important in order to contribute to defence responses. To date, the changes in the expression of PR1 and PDF 1.2 and contribution of (1,4)-β-glucanase enzyme in sunflower defence responses were not reported in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Most pathogenesis-related proteins have low molecular weight ranging from 8 kDa to 50 kDa [22]. In our previous study, we observed that the transcript abundance of two pathogenesis-related genes, PDF 1.2 and PR5-1, were higher in the partially resistant line compared to those in the susceptible line [23,24]. However, the identities of these new proteins need to be more clarify in future investigations.…”
Section: Protein Patterns Of Total Proteins In Susceptible and Partiamentioning
confidence: 99%
See 1 more Smart Citation
“…Most pathogenesis-related proteins have low molecular weight ranging from 8 kDa to 50 kDa [22]. In our previous study, we observed that the transcript abundance of two pathogenesis-related genes, PDF 1.2 and PR5-1, were higher in the partially resistant line compared to those in the susceptible line [23,24]. However, the identities of these new proteins need to be more clarify in future investigations.…”
Section: Protein Patterns Of Total Proteins In Susceptible and Partiamentioning
confidence: 99%
“…The Phloroglucinol-HCl staining also showed that more lignin deposition in the cell walls of xylem of partially resistant line after pathogen filtrate treatment. In our previous studies [23,24], we found that the activity of phenylalanine ammonia lyase enzyme (PAL) as well as shikimate dehydrogenase enzyme were much more pronounced in partially resistant line than susceptible line. In addition, some proteins such as peroxidase and laccase were only up-regulated in partially resistant line that might point out the critical role of the phenylpropanoid pathway in sunflower defense mechanism against S. sclerotiorum infection.…”
Section: Changes In Xylem Vessels Of Sunflower Lines After Culture Fimentioning
confidence: 99%
“…A few studies conducted in cultivated sunflower have exploited the advantages and sensitivity of this methodology to identify differentially-expressed genes under biotic or abiotic stress conditions 27,28 , and none of them addressed the S. sclerotiorum-sunflower interaction. Indeed, only two low-throughput transcriptomic studies have focused on this pathosystem 29,30 . In addition, most transcriptomic analyses of Sclerotinia infection were made with data obtained from symptomatic plants [20][21][22] .…”
mentioning
confidence: 99%